QUALITY OF LIFE AFTER CATARACT SURGERY IN PATIENTS WITH AGE-RELATED MACULAR DEGENERATION: A LITERATURE REVIEW - Syahruzad, Rosa; Widyawati, Syska; Wildan, Arief (Majalah Oftalmologi Indonesia, 2023)
Objective: Age-related macular degeneration (AMD) is a common ocular disease that affects millions of people worldwide. Cataract surgery is one of the most performed surgical procedures in the world and is effective to improve visual function and quality of life (QOL) in individuals with cataracts. Both cataract and AMD are conditions that occur in late age. However, the presence of AMD may complicate the postoperative outcomes and quality of life (QOL) of these patients. This review aims to examine the impact of cataract surgery on the QOL of patients with AMD. Methods: A search of the literature was conducted using electronic databases. Studies were included if they evaluated QOL outcomes in patients with AMD who underwent cataract surgery. Result: The results of the review suggest that cataract surgery can improve visual acuity and QOL in patients with AMD. However, the degree of improvement is influenced by the severity of AMD. Patients with mild to moderate AMD tended to have greater improvements in QOL and visual acuity compared to those with advanced AMD. Incidentally, it is still cost effective to perform cataract surgery in patients with advanced AMD. Conclusion: Overall, cataract surgery is found to be able to improve QOL and visual acuity in patients with AMD. Nevertheless, individual characteristics including severity of AMD must be considered to optimize the outcomes. Further research, particularly with longer follow up times, is needed to determine the long-term effects of cataract surgery on QOL in patients with AMD.